Modulation of the Apoptosis Gene Bcl-x Function Through Alternative Splicing - Stevens, Megan; Oltean, Sebastian (Frontiers in Genetics, 2019)
Apoptosis plays a vital role in cell homeostasis during development and disease. Bcl-x, a member of the Bcl-2 family of proteins, is a mitochondrial transmembrane protein that functions to regulate the intrinsic apoptosis pathway. An alternative splicing (AS) event in exon 2 of Bcl-x results in two isoforms of Bcl-x with antagonistic effects on cell survival: Bcl-xL (long isoform), which is anti-apoptotic, and Bcl-xS (short isoform), which is pro-apoptotic. Bcl-xL is the most abundant Bcl-x protein and functions to inhibit apoptosis by a number of different mechanisms including inhibition of Bax. In contrast, Bcl-xS can directly bind to and inhibit the anti-apoptotic Bcl-xL and Bcl-2 proteins, resulting in the release of the pro-apoptotic Bak. There are multiple splice factors and signaling pathways that influence the Bcl-xL/Bcl-xS splicing ratio, including SR proteins, hnRNPs, transcription factors, and cytokines. Dysregulation of the AS of Bcl-x has been implicated in cancer and diabetes. In cancer, the upregulation of Bcl-xL expression in tumor cells can result in resistance to chemotherapeutic agents. On the other hand, dysregulation of Bcl-x AS to promote Bcl-xS expression has been shown to be detrimental to pancreatic β-cells in diabetes, resulting in β-cell apoptosis. Therefore, manipulation of the splice factors, transcription factors, and signaling pathways that modulate this splicing event is fast emerging as a therapeutic avenue in the treatment of cancer and diabetes.